INOVASI PRODUK ES KRIM SUSU KAMBING ETAWA-UBI UNGU - Minar Ferichani; Darsono Darsono; Supanggyo Supanggyo (Caraka Tani: Journal of Sustainable Agriculture, 2017)
This productive research about “The Producing of Ettawa Goat Milk-Sweet Purple Potato Ice Cream” aimed to create a product made from ettawa goat milk which is delicious, nutritious, enjoyable, and marketable. The research in corporation with ettawa goat livestock owner’s wives which is united as KUBE (Corporative Business Association) Adi Jaya at Sayegan Sub-District, Sleman District, Yogyakarta, also partner with Jomint Company, was done in 2011. Research included program socialization to KUBE Adi Jaya officials; producing to get advance product; laboratory test at Lab. of Food Technology and Agricultural Product, Faculty of Agricultural Engineering, Gadjah Mada University; product packaging; disseminating to women as members of KUBE Adi Jaya and neighborhood; measuring of satisfaction to the product; and marketing. Quality measurement was done to measure satisfaction to product consisted of 4 indicators, those were taste, appearance, packaging, and contents (nutrition ingredient). The formula that was used was S = P/E which was a comparison among the expecting product (E) and the fact of product/product performance (P), in this case about how product showed the performance as real to compete with E. This formula was a modified concept by Kotler that states S = f(E,P). The criteria which was used was if S or Sav ≥ 1, it mean the product had high level of satisfaction; moderate if 0.7 < x < 1; and low if ≤ 0.7. Competitor product as E was an establish product, it was Walls ice cream as a product which was produced by Unilever Company, and our advance product as P. The research results show that the product contents complete nutrition. Contents of Cvitamin, protein and fiber function to protect and increase consumer’s healthy. Product also contents carotene, antioxidant and antocyanin that function to prevent cancer and cell degenerative process. Based on perspective about contents, the product is “ready” to be competed with ice cream which has established. The highest value of Sav is gained on contents (1,24), followed appearance (0,997), taste (0,983), and packaging (0,974). Level of respondent satisfaction to contents of etawa goat milk – sweet purple potato ice cream included high caused > 1, while to three others elements included moderate-high caused close to 1. Totally, Sav value that is achieved is 1.038, it means the product can satisfy the consumers in high level caused > 1. The product has capacity to compete even more satisfy than Walls ice cream based on product perspective (element of marketing mix). The product gets positive responses from members of KUBE Adi Jaya and others dissemination participants, also shops as partners of Jomint.